2015
DOI: 10.1111/1346-8138.12847
|View full text |Cite
|
Sign up to set email alerts
|

Favorable response to composite treatment including infliximab in a case of granulomatous cheilitis with Crohn's disease

Abstract: chest and groin was also sutured. Eight months later, skin ulcers appeared on the surgical scar of the forehead, nasolabial groove and chest, but not on the groin. Physical examination revealed a large, deep ulceration with elevated edematous borders (Fig. 1c,d). The ulcer was reddish and granular on the surface and surrounded by erythema. Bacterial cultures from superficial pus showed Pseudomonas aeruginosa, for which oral antibiotics resulted in no effect. Laboratory examination showed an increased number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“… 9 There were 12 additional published clinical cases (eight with CD) reporting successful treatment of cheilitis granulomatosa with infliximab, especially in childhood. 10 , 13 22 Kakimoto et al reported a patient with cheilitis without CD in which infliximab induced a good initial response but triggered an acute infusion reaction; remission was achieved after switching to adalimumab. 24 Gaya et al reported a case of isolated cheilitis successfully treated with infliximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 There were 12 additional published clinical cases (eight with CD) reporting successful treatment of cheilitis granulomatosa with infliximab, especially in childhood. 10 , 13 22 Kakimoto et al reported a patient with cheilitis without CD in which infliximab induced a good initial response but triggered an acute infusion reaction; remission was achieved after switching to adalimumab. 24 Gaya et al reported a case of isolated cheilitis successfully treated with infliximab.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 1 we summarize the characteristics of patients with granulomatous cheilitis, with or without coexistent CD, treated with biologics. 4,9,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] There was a clear predominance of cheilitis in children and young adults (mean age 26 years, SD 15), and 55% of the patients were female. Dupuy et al have reported a greater male predominance and a young age of onset in CD patients who present with oral manifestations.…”
Section: Granulomatous Cheilitis Originally Described Bymentioning
confidence: 99%